2016
DOI: 10.1371/journal.pone.0168051
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Inhalation Exposures Associated with Contamination Events in Water Distribution Systems

Abstract: When a water distribution system (WDS) is contaminated, short-term inhalation exposures to airborne contaminants could occur as the result of domestic water use. The most important domestic sources of such exposures are likely to be showering and the use of aerosol-producing humidifiers, i.e., ultrasonic and impeller (cool-mist) units. A framework is presented for assessing the potential effects of short-term, system-wide inhalation exposures that could result from such activities during a contamination event.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Data are not available for the types of water that consumers actually use to fill their ultrasonic humidifiers. As it requires approximately 2.5 L of water per 8-h cycle, it is likely that consumers may use local tap water for convenience ( Davis et al., 2016 ) even though about three decades ago the United States Environmental Protection Agency ( USEPA, 1991 ) recommended using distilled or low mineral water. Select ultrasonic humidifiers manufacturers make recommendations of water type to use in their products.…”
Section: Introductionmentioning
confidence: 99%
“…Data are not available for the types of water that consumers actually use to fill their ultrasonic humidifiers. As it requires approximately 2.5 L of water per 8-h cycle, it is likely that consumers may use local tap water for convenience ( Davis et al., 2016 ) even though about three decades ago the United States Environmental Protection Agency ( USEPA, 1991 ) recommended using distilled or low mineral water. Select ultrasonic humidifiers manufacturers make recommendations of water type to use in their products.…”
Section: Introductionmentioning
confidence: 99%
“…Except as noted, all simulations used a hydraulic time step of 3600 s. Various water-quality time steps were used for time-driven simulations to determine the influence of the time step on the MBR and the constituent concentrations. The default water-quality time step in EPANET is 300 s, as noted above; however, some studies, e.g., Diao et al (2016), Helbling and VanBriesen (2009), and Wang and Harrison (2014), use substantially longer time steps. Therefore, in our analysis we include water-quality time steps longer than the default value.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have shown that storage‐type water heaters can be modeled as a plug‐flow reactor (PFR) while turned on because of tank temperature stratification and because mixing does not usually occur during the first 80% of water volume used under low flow conditions (<2 gpm) (Brazeau & Edwards 2013a). However, best practices for water heater flushing should include turning the water heater off to avoid volatilization of potential harmful contaminants (Davis et al 2016, Omur‐Ozbek et al 2016, Casteloes et al 2015, Brazeau & Edwards 2013a); therefore, if the water heater is turned off and there is no temperature stratification, it is likely that mixing will occur during flushing, and a PFR model is not appropriate. In this case, a continuously stirred tank reactor (CSTR) model was evaluated, and researchers predicted that some flushing protocols would not have resulted in “safe” heaters (Casteloes et al 2015).…”
Section: Erratamentioning
confidence: 99%